Curriculum Development of the Faculties of the Health and Agricultural Sectors University of Gezira 15.12.2011 to 15.6.2012 - Ahmed Mirghani, Omer; Mohamed, Mohamed El Sanousi; Elamin Magbool, Osman Mohamed; Ali Omer, Mohamed Ahmed; ElGaili AbuBakr, Dia Eldin; Abbas, Abdulla ElFaki; Tag ElDin, Imad Mohamed; Mohamed, Yousif Fadl Alla; Mohamadani, Ahmed Abdulla; ElTom, Hashim; Hassan Arabi, Omer (مجلة الجزيرة للعلوم الصحية; مجلد 10 عدد 1 (2014), 2014)
The University of Gezira adopts nobel goals, community orientation and community development- and it set curricula capable of achieving those goals which are essential for sustainability of its excellence. Periodic development, upgrading and modernization of curricula is a fundamental requirement for all universities; knowledge is growing and changing very fast, also there are rapid changes in community needs and expectations and hence  graduates should be equipped with competencies which enable them to contribute significantly and efficiently in the total development of their societies. The University has a wealth of experience in development of its curricula since its foundation and hence it included it as one of the main four components of the University Development Project. The project is sponsored by the Islamic Bank for Development-Jeddah and the Ministry of Finance Sudan and has been launched in December 2011. The Project aimed to develop the Faculties of agricultural and health sectors- curricula, manpower and infrastructure. Those sectors were chosen to be sectors of excellence for students in the Islamic countries. The Vice Chancellor of the University of Gezira formed a committee to manage the whole task of development of all the curricula of the faculties in the health and agricultural sectors; Medicine, Medical Laboratory Sciences, Animal Production, Veterinary Medicine, Applied Medical Sciences, Dentistry, Pharmacy, Health and Environmental Sciences, Agricultural Sciences. The committee set the justifications, determined its strategies and designed the process of its work. The whole task was accomplished in the stipulated time - 4 months.